Management of Fracture of Shaft of Humerus with Intramedullary Interlocking Nail (Journal of Fatima Jinnah Medical University, 2018)
Background: Trauma has been one of the major causes of morbidity and mortality and the resultant bony injury if any really brings very tough time to the entire family because the patient has to face prolonged immobilization and loss of wages. The stiff joints and functional disability are common post-injury sequelae. Humeral shaft fractures are not very common. The middle third of the shaft is the usual target site and the high energy trauma is generally required to break it. Traditionally the non-operative measures i.e. hanging cast or brace have been used to treat humeral shaft fractures. Objectives: To analyze the results of fixation of the shaft of humerus by rigid interlocking intramedullary nailing, to determine the safety, simplicity and reliability of the method and its effect on shoulder and elbow joint function. Patients and Methods: This prospective randomized study consisted of fifty patients of humeral shaft fractures managed by intramedullary interlocking nail and was carried out at Department of Orthopedics, Social Security Teaching Hospital, Lahore from 1st January 2007 to 31st December 2010. The adult patients aged above 20 years, polytrauma and diaphyseal fractures of humerus were included in the study. Patients with previous osteomyelitis of shaft of humerus, proximal fractures within 2 cm of surgical neck and those within 5 cm of junction of diaphyses and metaphyses on both AP and lateral radiographs and pathological fractures were excluded from the study. Open fractures with segmental bone loss were bone grafted at the time of delayed closure, whether treated with a nail or plate, because the study protocol directed that no bone grafting be performed during the initial stabilization procedure. Results: Ninety percent of the patients operated with interlocking intramedullary nailing for humerus had callus formation within 8 weeks and 10% requiring more than 8 weeks. Post-operatively the regain range of motion of shoulder including abduction and external rotation was satisfactory. The rate of radial nerve palsy following surgery was only 2%. Conclusion: The technique interlocking intramedullary nailing plays a key role in the management of humeral shaft fractures. Its relative simplicity, firm fixation, lesser complications, early use of extremity and cost effectiveness of implant are the golden landmarks.
Keywords: Humeral shaft fractures, Rigid intramedullary fixation, Antegrade nailing, No external protection